A drug interaction study investigating the effect of Rifabutin on the pharmacokinetics of Maraviroc in healthy subjects - Ghannad, M.; Dennehy, M.; la Porte, C.; Seguin, I.; Tardiff, D.; Mallick, R.; Sabri, E.; Zhang, G.; Kanji, S.; Cameron, D. W. (PloS one, 2019)
Effects of steady-state rifabutin on the pharmacokinetics of steady-state maraviroc were investigated in fourteen healthy adult female and male volunteers. Maraviroc 300 mg twice daily (BID) was given orally with food for fifteen days. On day six, rifabutin 300 mg once daily (QD, P.O.) was added to the regimen. Formal pharmacokinetic (PK) sampling was performed on days five and fifteen. Individual plasma drug concentration-time data for maraviroc, and rifabutin on day fifteen, were obtained using validated High Performance Liquid Chromatography (HPLC) tandem Mass Spectrometry (MS/MS). Rifabutin steady state exposure was comparable to data in the literature. Maraviroc area under the curve (AUC) and minimum plasma concentration (Clast or Cmin) were reduced by 17% and 30% respectively when co-administered with rifabutin. No unexpected or serious adverse eventsoccurred. Based on the reduced exposure of maraviroc observed in this study, increasing the dose of maraviroc may be studied to normalize its moderately reduced exposure following rifabutin co-administration, a moderate inducer of CYP3A4.